Performance of a cluster of multi-anode photomultipliers equipped with lenses for use in a prototype RICH detector - Albrecht, E; Baker, J; Barber, G; Bibby, J; Calvi, M; Charles, M; Duane, A; Easo, S; Eisenhardt, S; Eklund, L; French, M; Gibson, V; et al. (2002)
A cluster of multi-anode photomultiplier tubes (MaPMTs) equipped with focusing lenses in front of the tubes was tested in a prototype ring imaging Cherenkov (RICH) detector in a charged particle beam. The readout electronics were capable of capturing the data at 40MHz. The effects due to charged particles and magnetic field on the MaPMT performance were also studied. The results are used to evaluate the MaPMT as a possible photodetector for the LHCb RICH detectors. © 2002 Elsevier Science B.V. All rights reserved.